Reasons Behind Generation Z Nursing Students' Intentions to Leave their Profession: A Cross-Sectional Study - Jaseon Kim MSN; Duckhee Chae PhD; Jae Yong Yoo PhD (SAGE Publishing, 2021)
This study aims to identify predictors of turnover intention within 2 years of employment among 3rd and 4th grade Generation Z nursing students. Turnover intention is a multi-stage process ranging from mere desire, to serious thoughts, decision-making, and actual planning. Previous studies have focused on identifying the factors affecting turnover intention among practicing nurses. However, undergraduate nursing students also contemplate their decision to stay or leave the nursing profession after graduation. This cross-sectional descriptive study recruited 210 nursing students from 3 colleges in South Korea. A self-administered survey was conducted using the Career Preparation Behavior Scale, the Calling and Vocational Questionnaire, the Social Responsibility Scale, and the Revised Self-Leadership Questionnaire. Four questions were used to explore participants' turnover intention, their motivation for studying nursing, their major satisfaction, and their clinical experience satisfaction. Descriptive and multiple logistic regression statistics were obtained using SPSS. Of the participants, 17.6% had turnover intention within 2 years of employment. Multiple logistic regression analysis indicates that clinical experience satisfaction is the only significant predictor. In the univariate analysis, nursing students who had turnover intentions were less likely to practice career preparation behaviors and had lower levels of vocational consciousness and social responsibility. To keep a proficient nursing workforce in the profession, professional commitments from universities and hospital institutions are needed to provide quality clinical learning experiences for nursing students. Further prospective study is needed to observe how Generation Z undergraduate students' turnover intentions change and what factors influence this process.